Penyuluhan Mitigasi Bencana Pada Anak Usia Dini di Desa Rawan Longsor Medowo Kediri Jawa Timur - Try Heny Aprilia; Adinda Maharani Laila Putri Warma; Amelia Putri H.; Cindy Febrianti E.P.; Devi Ayu K.; Mohammad Rico R.H.; Shella Dwiyanti; Sinta Kurnia S.; Su’da Rofifah N.H.; M Thoriqul Huda (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: The fact that Indonesia is a disaster-prone country is a truth that we cannot ignore; of course, various coping mechanisms have been prepared by related parties so that we can prevent more significant impacts as early as possible. Disaster mitigation counseling in disaster-prone areas is one of the efforts to minimize the incidence of substantial casualties due to the effects of disasters. Medowo is one of the areas in a disaster-prone area with the contour of the mountainside area. Method: Mitigation counseling is carried out by IAIN Kediri students in collaboration with community servants, related parties, and the local community, with 20 people. The PAR (Participatory Action Research) approach is used in this activity to conduct counseling on natural disaster mitigation in early childhood. Results: The results of the service showed that the children liked the counseling model that used virtual videos about the importance of understanding the signs of natural disasters, then the children also practiced directly on efforts to prevent natural disasters, as well as what actions need to be taken if they see victims of natural disasters. Conclusion: Natural disasters are inevitable, but preventive measures must be taken to overcome the large number of casualties.